Synthesis, Characterization, Antimicrobial and Anticancer Activities of 14-Membered Macrocyclic Schiff Base Metal Complexes - Palanimurugan, A.; Kulandaisamy, A. (Asian Journal of Chemistry, 2018)
New cationic 14-membered macrocyclic Schiff base metal complexes have been synthesized by condensation of benzalidene-curcuminyl-4-iminoantipyrine and 2,6-diaminopyridine. Structural characterization of the compounds was done using elemental analysis, molar conductivity, magnetic susceptibility, Mass, SEM, XRD, 1H NMR, UV-visible, IR and EPR spectra. X-ray diffraction patterns suggested that the size of Schiff base is reduced due to chelation by the metal ion. Different morphologies of synthesized compounds were identified by SEM images. Magnetic moment values, UV-visible and IR spectral studies confirms the square planar geometry of chelates. However [VOL]Cl2 exists in octahedral geometry. Electron spin resonance spectra parameters of [CuL]Cl2 and [VOL]Cl2 complexes were well coinciding with proposed geometries. The in vitro biocidal activities of the compounds were done against some bacterial and fungal strains by disc diffusion method. Anticancer activity of Schiff base and copper complex were carried out by MTT method which reveals that the inhibition against the growth of breast cancer cell line culture for chelate is higher than Schiff base.